Potensi Energi Angin pada Sisi Siku Atap Gedung Tinggi - Wildane Aryabathi; Erwin Erwin; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2021)
Wind is moving air caused by the earth's rotation and also because of the difference in air pressure around it. The wind flows that occur include laminar flow and turbulent flow. Judging from the effect of spreading its direction, the wind that passes through a building, its flow will split into horizontal and vertical axes and pass along the geometry and structure of the building. This happens because the wind speed increases due to the increased wind pressure along the side of the building. Departing from this hypothesis, this research was conducted to compare the velocity potential on the angle side of the building roof with the speed at the top of the building (Rooftop) as a starting point for the development of new renewable energy engineering, especially wind energy. This experiment was conducted at the Dean Building of the Faculty of Engineering, Sultan Ageng Tirtayasa University, Cilegon, Banten. After conducting experiments with reference to the International Electrotechnical Commission (IEC) 61400-12-1 standard, this research found that on the angle side of the building the average and maximum velocity are higher than those on the roof of the building, also the wind energy potential is higher, amounting to ≥20.94%. In terms of Daily Wind Energy Potential, the elbow side of the building is proven to be more efficient with an increase in efficiency of 42.2%.